Mengenal Lebih Dekat Apa Itu Penyakit Kondiloma Akuminata - Padila, Padila; Andri, Juli; Yanti, Lussyefrida; Yanuarti, Riska; Sinta, Fera; Novitasari, Selvia (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2025)
Condyloma acuminata (KA), also known as genital warts or genital warts, is a sexually transmitted disease caused by the Human Papilloma Virus (HPV). The HPV subtypes that most often cause KA are 6 and 11, while subtypes 16 and 18 have the potential to cause cervical cancer. In the United States, there are more than 19.7 million new cases of sexually transmitted infections each year, with 14.1 million cases being HPV infections. In Indonesia, KA was ranked third largest in 12 teaching hospitals in the 2007-2011 period, with a high prevalence in the cities of Medan, Jakarta, Bandung, Semarang, Jogja and Denpasar, especially among those aged 25-45 years. HPV transmission occurs through sexual contact and can also occur through direct contact with contaminated objects. This disease can attack various genital areas and shows symptoms such as warts, itching, and discomfort. State Senior High School (SMAN) 3 Bengkulu City needs health education to increase students' awareness about the importance of maintaining the health of the genital area. Many students still take their genital health for granted, which can trigger deviant behavior. Therefore, the Service Team from the Faculty of Health Sciences, Muhammadiyah University of Bengkulu conducted outreach at the school in July 2024. This activity included a site survey, education about KA prevention, and evaluation. The results of the counseling show an increase in students' understanding of KA. The enthusiasm from the school and students is very good. Suggestions are given for the school to better control and accompany students to prevent trivialization of the disease, and students are expected to be more social and sensitive to the environment.